Zaznava vodij o povezanosti osebnostnih lastnosti z osebno učinkovitostjo in timsko uspešnostjo - Novak, Igor (Teorija in praksa, 2021)
In the field of work psychology, researchers have paid substantial attention to the study of personality traits in relation to work efficiency. The article forms an integral part of a larger doctoral study and is considered as a pilot study that aims to shed light on the subjective beliefs held by leaders concerning the relationship of personality traits between personal performance and team performance and to describe the difference between the findings of this qualitative research and quantitative research. We used a qualitative research design with a view to finding answers to key questions in a sample of 18 leaders (managers) using the method of a semi-structured interview. The results showed the managers most often highlight the personality trait of agreeableness as an important factor influencing personal effectiveness and team performance. They believe the personality traits of openness, extraversion and conscientiousness also influence the constructs under study. Compared to quantitative research, these leaders attach much more importance to agreeableness than to extroversion and place less emphasis on the importance of neuroticism. The pilot study showed that, according to the leaders, personality traits affect both personal and team performance.
Keywords: delovna učinkovitost; osebne lastnosti; Osebnost; percepcija; Psihologija dela; subjektivna prepričanja; timska uspešnost; Učinkovitost; Vodenje; vodje